A low-profile wideband circularly polarized CPW slot antenna - Gharaati, Alireza; Ghaffarian, Mohammad Saeid; Saghlatoon, Hossein; Behdani, Mahdi; Mirzavand, Rashid (International journal of electronics and communications, 2021)
In this paper, a wideband compact circularly polarized (CP) antenna is presented to cover radio frequency identifications (RFID), global navigation satellite system (GNSS), wireless local area network (WLAN), and worldwide interoperability for microwave access (WiMAX) frequency bands of interest. The antenna comprises of three asymmetrical rectangle slots, which are fed at the open end of a coplanar waveguide (CPW) line. Due to a very simple structure, the design and fabrication processes for different frequencies are straightforward. The overall size of the compact designed antenna is about 0.27λ0×0.26λ0×0.002λ0 at the lowest frequency of the operating bandwidth. To demonstrate the performance of the proposed antenna, the measured 10-dB impedance bandwidth of 129.5 % (0.9–4.2 GHz), axial ratio bandwidth (ARBW ≤ 3-dB) of 112 % (0.9–3.2 GHz), and maximum gain of 5 dBic are achieved. The 3-dB RHCP gain bandwidth is also achieved from 0.9 GHz to 3.05 GHz (108 %). The achieved characteristics of the proposed antenna indicate the advantage of the designed antenna over the state-of-the-art wideband antennas in terms of impedance bandwidth, ARBW, and size simultaneously. The overlapping bandwidth of the 10-dB impedance bandwidth and the 3-dB axial ratio bandwidth is about 112 % (0.9–3.2 GHz).